New soluble angiopoietin analog of Hepta‐ANG1 prevents pathological vascular leakage. Issue 1 (10th October 2020) - Liu, Pan; Ryczko, Michael; Xie, Xinfang; Baardsnes, Jason; Lord‐Dufour, Simon; Duroche, Yves; Hicks, Emily Anne; Taiyab, Aftab; Sheardown, Heather; Quaggin, Susan E.; Jin, Jing
Abstract: Vascular leak is a key driver of organ injury in diseases, and strategies that reduce enhanced permeability and vascular inflammation are promising therapeutic targets. Activation of the angiopoietin‐1 (ANG1)‐Tie2 tyrosine kinase signaling pathway is an important regulator of vascular quiescence. Here we describe the design and construction of a new soluble ANG1 mimetic that is a potent activator of endothelial Tie2 in vitro and in vivo. Using a chimeric fusion strategy, we replaced the extracellular matrix (ECM) binding and oligomerization domain of ANG1 with a heptameric scaffold derived from the C‐terminus of serum complement protein C4‐binding protein α. We refer to this new fusion protein biologic as Hepta‐ANG1, which forms a stable heptamer and induces Tie2 phosphorylation in cultured cells, and in the lung following intravenous injection of mice. Injection of Hepta‐ANG1 ameliorates vascular endothelial growth factor‐ and lipopolysaccharide‐induced vascular leakage, in keeping with the known functions of Angpt1‐Tie2 in maintaining quiescent vascular stability. The new Hepta‐ANG1 fusion is easy to produce and displays remarkable stability with high multimericity that can potently activate Tie2. It could be a new candidate ANG1 mimetic therapy for treatments of inflammatory vascular leak, such as acute respiratory distress syndrome and sepsis. Abstract : The natural ANGPT1 does not circulate freely in the bloodstream but instead binds avidly to ECM, which makes the design of an effective ANGPT1 therapy challenging. In this study, we replaced the extracellular matrix (ECM) binding and oligomerization domain of ANGPT1 with a heptameric scaffold peptide derived from the C‐terminus of serum complement protein C4‐binding protein α (C4BP). Our experimental data shows that systemic administration of this stable heptameric complex activates Tie2 and ameliorates inflammatory vascular leakage in vivo.